2015
DOI: 10.17261/pressacademia.2015414540
|View full text |Cite
|
Sign up to set email alerts
|

Vision and Its Impact on Team Success

Abstract: A strong vision is a main predictor for both organizational and team success. Although many studies conclude that vision is important at the organizational level, the impacts of vision on innovation/teams have received far less attention. The purpose of this paper is to discuss vision components and explore its impacts on team performance. After studying the vision on a series of 12 innovations at three companies (Apple, IBM, and HP), we empirically tested the impact of the three components of vision on overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
(94 reference statements)
1
3
0
Order By: Relevance
“…Our findings have implications for owners and managers involved in the manufacturing sector, in line with results reported in the literature. The most important result of our study is the significant positive effect of strategic innovation on SMEs' competitive advantage, in line with a series of high profile studies (Lilly and Juma, 2014;Lynn and Kalay, 2015). This result shows that if manufacturing SMEs invest in obtaining innovation technologies they can achieve better performance and a competitive position in the market.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings have implications for owners and managers involved in the manufacturing sector, in line with results reported in the literature. The most important result of our study is the significant positive effect of strategic innovation on SMEs' competitive advantage, in line with a series of high profile studies (Lilly and Juma, 2014;Lynn and Kalay, 2015). This result shows that if manufacturing SMEs invest in obtaining innovation technologies they can achieve better performance and a competitive position in the market.…”
Section: Discussionsupporting
confidence: 86%
“…We demonstrated that team leaders have a leading role in guiding the team vision. Research has shown that creating clarity about the team vision is significantly associated with positive team performance 67 . This could also facilitate role clarification, because developing goals related to the team vision enables each team member to understand the direction in which to move 68 and to clarify their role in this journey 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that creating clarity about the team vision is significantly associated with positive team performance 67 . This could also facilitate role clarification, because developing goals related to the team vision enables each team member to understand the direction in which to move 68 and to clarify their role in this journey 67 . An increased common awareness is required among HCPs that dementia is a life-limiting disease and that the integration of a PC approach is necessary in dementia care 69 .…”
Section: Reflection Meetingmentioning
confidence: 99%
“…239-269 ISSN 2174-548Xinnovations on the performance of SMEs. Further, the study ofKalay and Lynn (2015) has recommended that performance is impacted by companies' innovation strategies. Studies byMazzanti et al (2006),Bowen et al (2010),Gunday et al (2011) performance are positively linked.…”
mentioning
confidence: 99%